2023
DOI: 10.1101/2023.02.07.527531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selection of ade novogene that can promote survival ofE. coliby modulating protein homeostasis pathways

Abstract: Cells sometime adapt to challenging environments by turning non-functional loci into functional genes in a process termedde novogene birth. But how proteins with random amino acid sequences integrate into existing cellular pathways to provide a benefit remains poorly understood. Here, we screened ~108random genes for their ability to rescue growth arrest ofE. colicells producing the ribonuclease toxin MazF. Approximately 2,000 random genes could promote growth by reducing transcription from the promoter drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…However, to which extent is yet unknown, [8][9][10] Several studies have previously utilized randomly generated proteins to draw conclusions about the origin, structure, and activities of de novo proteins. [11][12][13][14][15][16][17] De novo proteins, particularly those of a more recent origin, have been found to differ from evolutionary conserved proteins and instead exhibit a similarity to random proteins, as they have not yet been subjected to natural selection. 8,9,13 Libraries of random sequences constrained only by a close to natural distribution of amino acids have been shown to form secondary structural elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to which extent is yet unknown, [8][9][10] Several studies have previously utilized randomly generated proteins to draw conclusions about the origin, structure, and activities of de novo proteins. [11][12][13][14][15][16][17] De novo proteins, particularly those of a more recent origin, have been found to differ from evolutionary conserved proteins and instead exhibit a similarity to random proteins, as they have not yet been subjected to natural selection. 8,9,13 Libraries of random sequences constrained only by a close to natural distribution of amino acids have been shown to form secondary structural elements.…”
Section: Introductionmentioning
confidence: 99%
“…Devoid of sequence homology outside their evolutionary trajectory, de novo proteins are considered to be distant in sequence space from evolutionarily conserved proteins and might instead resemble unevolved random proteins. However, to which extent is yet unknown, 8–10 Several studies have previously utilized randomly generated proteins to draw conclusions about the origin, structure, and activities of de novo proteins 11–17 . De novo proteins, particularly those of a more recent origin, have been found to differ from evolutionary conserved proteins and instead exhibit a similarity to random proteins, as they have not yet been subjected to natural selection 8,9,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Carvunis et al 16 found de novo cORFs are enriched for the GO term 'response to stress'. Other studies showed examples of how de novo ORFs could be involved in stress response 29,64 or homeostasis 64,65 . For instance the de novo antifreeze glycoprotein AFGP allows Arctic codfish to live in colder environments 29 or MDF1 in yeast, provides resistance to certain toxins and mediates ion homeostasis 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Future studies that leverage the ever-increasing global metagenomic sequences will be useful to tackle that question. Additionally, experimental evidence shows that the emergence of functional proteins via de novo gene evolution from noncoding sequences can provide adaptation in Escherichia coli (Babina et al 2023; Frumkin & Laub 2023). Thus, de novo evolution may be more plausible, and prevalent, than usually assumed.…”
Section: Discussionmentioning
confidence: 99%